Legal Implications Access and Benefit-Sharing of Genetic Resources to Supporting the SDGs - Susanti, Susi; Hieronymus Soerjatisnanta; Ria Wierma Putri (Dinasti Research, 2025)
The protection of genetic resources is fundamental for achieving the Sustainable Development Goals (SDGs), especially in supporting food security, conserving biodiversity, and fostering global partnerships. As Indonesia possesses vast biodiversity, including high-value genetic resources, their preservation has become increasingly important. The Access and Benefit-Sharing (ABS) mechanism, regulated under the Nagoya Protocol, provides a legal framework that balances access to genetic resources with fair and equitable benefit-sharing. ABS directly supports SDG 2 (Zero Hunger) by enhancing food resilience, SDG 15 (Life on Land) by preserving ecosystems, and SDG 17 (Partnerships for the Goals) by fostering international cooperation. However, the implementation of ABS in Indonesia faces significant challenges, such as fragmented national policies, complex inter-ministerial coordination, and the lack of a unified regulatory system. These challenges necessitate strategic recommendations to strengthen ABS, including improving national policies, enhancing coordination, and promoting international partnerships. Strengthening ABS frameworks can better safeguard genetic resources from exploitation, ensure fair benefit distribution to local communities, and promote sustainable innovation and environmental practices. This study analyses the relationship between genetic resource protection, food security, and the critical role of ABS in achieving SDGs. It concludes that addressing legal, institutional, and policy gaps in ABS implementation is essential for harnessing the full potential of genetic resources in supporting the 2030 SDGs. Recommendations include developing comprehensive national legislation, fostering collaboration, and strengthening enforcement to ensure long-term sustainability and global equity in genetic resource management.